Anatomic Fibular Collateral Ligament and Anterior Cruciate Ligament Reconstruction With Concomitant Biceps Femoris Avulsion Repair - Mark T. Banovetz BS; Jacob A. Braaten BA; Morgan D. Homan DO; Jill K. Monson PT; Nicholas I. Kennedy MD; Robert F. LaPrade MD, PhD (SAGE Publishing, 2023)
Background: Injuries to the fibular collateral ligament (FCL) seldom occur in isolation and may present with a concomitant injury to the biceps femoris tendon and anterior cruciate ligament (ACL). Injuries to structures of the posterolateral corner (PLC) lead to varus and rotational instability of the knee, subjecting the cruciate ligaments to increased forces that may result in graft failure. Therefore, reconstruction of these structures should be performed concurrently with the ACL. Indications: Grade III FCL injuries heal poorly without operative treatment and often result in residual varus instability of the knee that increases medial knee compartment forces, and forces on both the native ACL and the graft status post ACL reconstruction. Therefore, preservation of biomechanical stability and long-term health of the knee are reliant on addressing injuries to the PLC surgically. Technique Description: A key concept of this surgical technique is a meticulous peroneal nerve neurolysis in the setting of altered biceps femoris anatomy, and the proper order of the surgical steps for tunnel creation, graft passage, and fixation and suture anchor insertion to achieve optimal patient outcomes. The described technique involves a lateral surgical approach, peroneal neurolysis, and preparation of fibular and femoral FCL tunnels, followed by a Bone-patellar tendon-bone graft (BTB) graft harvest. Attention is then turned to intra-articular work including the diagnostic arthroscopy, femoral and tibial tunnel preparation, passage of the ACL graft, and fixation of the grafts in femoral tunnels. Last, fixation is achieved in the following order: FCL graft on fibula, ACL graft on tibia, and biceps femoris tendon to fibular head. Results: Compared with the preoperative state, Moulton et al reported significant improvements in the average Lysholm and Western Ontario scores at 2.7 years postoperatively following anatomic FCL reconstrution. Furthermore, Thompson et al reported on primary suture anchor repair of distal biceps femoris in 22 elite athletes and reported that all patients had returned to their preinjury level of sporting activity at 2-year follow-up. Discussion: Anatomic reconstructions of the FCL and ACL, such as the one described in our technique, effectively restore near native knee biomechanics and offer superior clinical outcomes compared with nonanatomic-based FCL reconstructions. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.